Cancer diagnosis in Scottish primary care: Results from the National Cancer Diagnosis Audit. (10th March 2020) - Murchie, Peter; Adam, Rosalind; McNair, Emma; Swann, Ruth; Witt, Jana; Wood, Rose; Weller, David
Abstract: Objective: To characterize cancer diagnosis in Scottish primary care and draw comparisons with cancer diagnostic activity in England. Method: A national audit of cancer diagnosis was conducted in Scottish and English general practices. Participating GPs collected diagnostic pathway data on patients diagnosed in 2014 from medical records. Data were supplemented by linkage to national cancer registries. Analysis explored and compared patient characteristics, diagnostic intervals, and routes to diagnosis. Results: 7.7% of all Scottish general practices in 2017 provided data on 2, 014 cancer diagnoses. 71.5% of cases presented to GPs and 37.4% were referred using the "Urgent‐Suspected Cancer" route. The median primary care interval was 5 days (IQR 0‐23 days) and median diagnostic interval was 30 days (IQR 13‐68). Both varied by cancer‐site. Diagnostic intervals were longer in the most remote patients and those with more comorbidities. Scottish and English samples corresponded closely in key characteristics. Conclusions: Most people diagnosed with cancer in Scotland present to a GP first. Most are referred and diagnosed quickly, with variations by cancer‐site. Intervals were longest for the most remote patients. GPs in Scotland and England appear to perform equally but, in view of growing differences between health systems, future comparative audits may be informative.